Focusing on DNA Repair and Damage Tolerance Mechanisms in Mycobacterium tuberculosis: An Emerging Therapeutic Theme - Mittal, Pooja; Sinha, Rajesh; Kumar, Amit; Singh, Pooja; Ngasainao, Moses R.; Singh, Archana; Singh, Indrakant K. (Current Topics in Medicinal Chemistry, 2020)
Tuberculosis (TB) is one such disease that has become a nuisance in the world scenario and one of the most deadly diseases of the current times. The etiological agent of tuberculosis, Mycobacterium tuberculosis (M. tb) kills millions of people each year. Not only 1.7 million people worldwide are estimated to harbor M. tb in the latent form but also 5 to 15 percent of which are expected to acquire an infection during a lifetime. Though curable, a long duration of drug regimen and expense leads to low patient adherence. The emergence of multi-, extensive- and total- drug-resistant strains of M. tb further complicates the situation. Owing to high TB burden, scientists worldwide are trying to design novel therapeutics to combat this disease. Therefore, to identify new drug targets, there is a growing interest in targeting DNA repair pathways to fight this infection. Thus, this review aims to explore DNA repair and damage tolerance as an efficient target for drug development by understanding M. tb DNA repair and tolerance machinery and its regulation, its role in pathogenesis and survival, mutagenesis, and consequently, in the development of drug resistance.
Keywords: Drug resistance